Pieczęcie proboszczów - zapomniany dział sfragistyki : przyczynek do badań nad pieczęciami kleru parafialnego na przykładzie pięciu sigillów śląskich plebanów z początku XIV w. - Sobel, Jagna Rita (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The article raises the issue of medieval seals of parish priests, lesser known in Polish historiography. Modest to-date achievements of scholars in this field, research perspectives and postulates, as well as methodological conditions were discussed. Moreover, five Silesian parsons’ sigilla from the year 1312 were subject to analysis, which demonstrated that they constitute an excellent source of knowledge on mentality and personal features of their users, and even on the relations between them and other people or institutions; such knowledge is not always provided by other available accounts.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne